Incorporating the effects of country of ownership: a study of Australian brands - Cheah, Isaac; Phau, Ian (School of Marketing, Curtin Business School, 2008)
The paper proposes a research framework to study the influence of country of origin cues, consumer economic nationalistic and consumer ethnocentric tendencies toward product judgement of and the willingness to buy Australian brands. Categorization theory, confirmation bias and schema congruity principles form the theoretical bases. Both consumer economic nationalistic and consumer ethnocentric tendencies are separate constructs however are correlated. Symbolic and functional brand concepts are anticipated to reflect consumer schematic tendencies. Consumer knowledge is proposed to moderate the relationship between these cues and consumer?s willingness to buy Australian brands. The hypotheses will be tested with structural equation modelling. The main contributions of the proposed research are also delineated.